2015
DOI: 10.1074/jbc.m114.612903
|View full text |Cite
|
Sign up to set email alerts
|

TPX2 Inhibits Eg5 by Interactions with Both Motor and Microtubule

Abstract: Background: TPX2 is a mitotic microtubule-associated protein that regulates the kinesin, Eg5. Results: Full-length TPX2 is a more potent inhibitor of Eg5 velocity than truncated TPX2; differential regulation by TPX2 was not observed for monomeric Eg5. Conclusion: TPX2 inhibits Eg5 as a roadblock and by direct interaction with Eg5. Significance: TPX2 may contribute to the spatial and temporal regulation of the mitotic motor Eg5.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
37
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 45 publications
4
37
0
Order By: Relevance
“…We currently do not understand how the haspin-AURKC pathway is regulating MTOC clustering. One possible mechanism is that AURKC or its unknown binding partner could negatively regulate the affinity of Eg5 for microtubules as AURKA and TPX2 have been shown to do (Balchand et al, 2015;Giet et al, 1999). Although it was surprising that AURKC colocalized with MTOCs, this localization is consistent with reports demonstrating localization of human AURKC at centrosomes in cancer cell lines (Khan et al, 2011;Tsou et al, 2011).…”
Section: Discussionsupporting
confidence: 79%
“…We currently do not understand how the haspin-AURKC pathway is regulating MTOC clustering. One possible mechanism is that AURKC or its unknown binding partner could negatively regulate the affinity of Eg5 for microtubules as AURKA and TPX2 have been shown to do (Balchand et al, 2015;Giet et al, 1999). Although it was surprising that AURKC colocalized with MTOCs, this localization is consistent with reports demonstrating localization of human AURKC at centrosomes in cancer cell lines (Khan et al, 2011;Tsou et al, 2011).…”
Section: Discussionsupporting
confidence: 79%
“…, 2009) and used these cells to prepare cytoplasmic extracts for use in single-molecule total internal reflection fluorescence (TIRF) microscopy experiments (Figure 2A; Cai et al. , 2007; Balchand et al. , 2015).…”
Section: Resultsmentioning
confidence: 99%
“…This possibility is consistent with the observation that Eg5 prepared from interphase extracts, and thus lacking the mitosis-specific phosphorylation that is required for spindle microtubule binding (Blangy et al. , 1995), shows robust motility in vitro (Balchand et al. , 2015).…”
Section: Resultsmentioning
confidence: 99%
“…This equation was then used to determine the off-rate of TPX2 from the lattice (k off,TPX2 ) for use in our simulations (below). The median value of k off,TPX2 was 0.015 s, with a corresponding characteristic residence time of τ∼65 s on the lattice, suggesting that TPX2 turns over relatively slowly on microtubules (Balchand et al, 2015). Finally, uniform recovery of TPX2 fluorescence across the bleaching window suggested that TPX2 binds and unbinds, but perhaps does not efficiently diffuse, on the microtubule lattice (Fig.…”
Section: Mcherry-tpx2 Interacts With the Microtubule Lattice And Tipmentioning
confidence: 91%